Challenges and Issues in Mixed Marriage Between the Indonesian and Non-Indonesian Diaspora - Kalek, Sally (SMART: Journal of Sharia, Traditon, and Modernity, 2024)
This study examines the challenges and issues that arise in mixed marriages between Indonesian and non-Indonesian diaspora, especially from an Islamic perspective. This study highlights various issues faced by couples in mixed marriages, such as cultural differences, gender roles, religious views, and children's education as well as various identity issues for the couple. The research method uses a qualitative method through an in-depth literature review of primary sources that discuss marriage in Islam and the cultural challenges of mixed marriages. This study also looks at the acculturation process that occurs in mixed marriages and how Muslim couples maintain their religious identity amidst different socio-cultural pressures. The results of the study show that couples in mixed marriages are often faced with conflicts related to differences in cultural norms and values, especially in terms of food, clothing, and roles in the household. Differences in religious practices can trigger tension in relationships. Children from mixed marriages also often experience confusion about religious identity, which can affect their spiritual development. In conclusion, mixed marriages can be successful if couples can overcome their differences by understanding, respecting, and upholding Islamic values.Keywords: Cultural Identity, Culture and Tradition, Family Dynamics, Gender Equality, Mixed Marriage